Rasch Analysis and Differential Item Functioning of the Time Management Questionnaire among University Students - Shindi, Yousef Abu; Alkharusi, Hussain; Shebani, Zubaida; Kazem, Ali; Alsoudi, Sharif; Maqbali, Aisha Al; Al-Bahrani, Muna; Fahdi, Rashid Al; Al-Omari, Aieman A.; Alabri, Khamis (Journal of Posthumanism, 2024)
Time management, crucial for success in personal, professional, and social life, is frequently assessed using scales, with the Time Management Questionnaire (TMQ) being a widely used tool. This study examines the psychometric properties of the TMQ using Item Response Theory. Specifically, the Rasch model is applied to estimate item and examinee parameters, while confirmatory factor analysis is used to confirm the scale’s factorial structure. The study also investigates differential item functioning (DIF) for scale items with respect to respondent gender. A sample of 1026 university students was analyzed. The new proposed three-factor model was found to outperform the original model and a one-factor model. Rasch analysis confirms the items’ fit to the model. Additionally, significant DIF was identified across gender for six items, offering insights into refining the TMQ’s measurement accuracy. These findings enhance our understanding of time management as a construct and reinforce the TMQ’s reliability. Recommendations include further refinement of the TMQ and considerations of its moderating effects. The results highlight the importance of ongoing evaluation to ensure the TMQ’s validity and effectiveness in accurately assessing time management behaviors.